PENYULUHAN TENTANG PELUANG DAN TANTANGAN BERWIRAUSAHA BAGI MAHASISWA DI ERA NEW NORMAL - Fahmi Yahya; Dwi Mardhia; I Made Sentaya; I Gusti Made Sulindra; Tursina Ratu (FKIP Universitas Samawa, 2021)
Entrepreneurship is a suitable career for students as millennials. By becoming an entrepreneur, we can earn not only income for ourselves but can also make a positive contribution to our family, society, and country. The purpose of this community service activity is to provide understanding to students as the younger generation about the opportunities and challenges of entrepreneurship during the new normal, as well as to provide motivation to become a young entrepreneur. Activities are divided into three main stages, namely the preparation stage, implementation stage, and evaluation. The implementation of the activities took place in the 2nd Floor Hall of the Samawa University (UNSA) Rectorate. The event was conducted in the form of a seminar with a face-to-face method by following the covid-19 health protocol. The participants of the activity were 60 students from various representatives of student organizations within Samawa University. Activities ran smoothly and according to plan. Participants were very enthusiastic and followed the activity until the end. Activities like this are expected to become routine activities to increase student motivation in entrepreneurship.